Virtual masks in the masks in the BACCHAE by Georgia Spiropoulos - Spiropoulos, Georgia Spiropoulos Georgia; Georgaki, Anastasia Georgaki Anastasia (2010)
aspects on the interactive masks created by the composer Georgia Spiropoulos for the needs of the opera Les Bacchantes (Ircam, 2010). Bacchae is an opera for a single performer, tape and live electronics where the voice of the performer interprets four different roles with the interactive environment in Max/Msp. The virtual masks as a metaphor of Euripide’s dramatic personae and masks1 of the same actor. Are used as virtual scores which register the vocal trace of the performer and give further vocal agility, extensibility, mutation, multiplication and augmented vocality.